Pengaruh Harga, Promosi dan Kualitas Pelayanan Terhadap Keputusan Penggunaan Jassa CV Muda Art Project Event Organizer - Khotimah, Wirda; Sari, Dewi Comala (Civiliza Publishing, 2025)
The decrease in the number of clients at the event organizer CV Muda Art Project is a phenomenon in this study to determine the decision to use services. This study aims to determine the effect of price, promotion and service quality on the decision of event organizer service users CV Muda Art Project. The sample of this study was 66 service users taken from 2019 - 2023. Data collection was carried out through questionnaires distributed in the form of google forms via social media and through literature studies in the form of primary and secondary data. This study uses a quantitative research method with a descriptive research type that includes validity tests, reliability tests, classical assumption tests, hypothesis tests. The results of this study are that the price variable partially has a positive and significant effect on the decision to use services, the promotion variable partially has a positive and significant effect on the decision of service users, the service quality variable partially has a positive and significant effect. The results of the determination coefficient test (R2) show that the price, promotion and service quality variables have an effect on the decision to use services by 57.6% and the remaining 42.4% is influenced by other variables not examined in this study.